Mechanical and tribological behavior of Ti/TiN and TiAl/TiAlN coated austempered ductile iron - Colombo, Diego Alejandro (2018)
Bilayer Ti/TiN and TiAl/TiAlN coatings were deposited onto austempered ductile iron (ADI) substrates by cathodic arc deposition in an industrial device. Structure and mechanical properties of the coated samples were comparatively examined. Wear behavior of the coated samples was investigated in comparison with uncoated ADI by means of rolling contact fatigue (RCF) tests, performed in a flat washer type testing rig and using lubricated pure rolling conditions. RCF tests results were analyzed using the two-parameter Weibull distribution and the Weibayes method. The results indicate that TiN and TiAlN coatings grew with a cubic-NaCl type structure. The arithmetic average roughness of the coated samples is similar for both coating variants. The surface hardness and residual stresses are higher for the TiAl/TiAlN coated samples. The coating hardness and elastic modulus are also higher for TiAl/TIAlN. The critical loads at massive delamination and the evolution of the friction coefficients are quite similar for both coating variants. Regarding RCF, failures in coated samples were characterized by substrate spalling. No massive delamination was observed in Ti/TiN and TiAl/TiAlN coatings. The statistical analysis indicates that the deposition of Ti/TiN improves noticeably the RCF resistance of ADI while the deposition of TiAl/TiAlN does not produce significant changes. The properties mismatch between substrate and coating seems to play an important role in the RCF behavior of coated samples, since Ti/TiN coatings possess a lower mismatch with respect to ADI substrates as compared to TiAl/TiAlN.